Impact Of Service Quality On Students Satisfaction In Higher Education Institutions - Roohul Amin; Dr. Asma Khuwaja; NisarAfridi (Journal of Business & Tourism, 2020)
In prevalent competitive environment of higher education institutions it has become vital for the institutional management to pursue for attainment of students satisfaction and maintain it throughout their stay in the institution during the course of study. Besides many predictors, the service quality is considered very vital factor in education sector to ensure students satisfaction all along their learning stage. Therefore, this research study aims to measure the relationship between the service qualities of higher education institutions with their customers (students) satisfaction. The service quality of higher education is determined by measuring various dimensions of service quality such as; the tangibility of institution and its infrastructure, reliability in its service delivery, responsiveness of its service providers, assurance and empathy. The research furthers its measurement of relationship of each dimension of service quality with students satisfaction level with a view to ascertain significance of each or otherwise. The research intends to investigate students of public and private sector universities of Khyber Pakhtunkhwa. The research is not only expected to determine the prevalent level students satisfaction and service quality of higher education, but also help to draw a comparative analyses between the public and private sector in this regard. The research would help the management of higher education institutions to revisit and regulate their strategies to deliver better service quality to its customers by focusing each dimension of the service quality individually.